SISTEM MONITORING OTOMATIS IRIGASI PERTANIAN UNTUK MEMENUHI KEBUTUHAN AIR DAERAH PESAWAHAN - Mulyadi Mulyadi; Dadi Rosadi; Rini Risanti (Jurnal Computech & Bisnis (e-Journal), 2022)
This study aims to design and implement a circuit that functions to open and close the rice field irrigation door automatically. By using an automatic irrigation control system in order to make it easier for farmers to control the entry of water in the irrigation flow. With the development of technology, the existence of sensors and microcontrollers, it is easier to make automatic irrigation controllers using ultrasonic sensors. To read the water distance when the water distance is normal, the servo motor will open 180º. And if the water experiences a height within a certain distance, the servo motor will move to close. As a water distance controller, the ultrasonic sensor reads the water distance which will be displayed on the LCD screen. The adapter functions as a supply of AC (220V) to DC (12V) current which is used to supply current to the Arduino. In order for the irrigation flow to function automatically, an Arduino UNO R3 microcontroller is needed to receive data sent from the servo motor, ultrasonic sensor. So that this tool can be programmed to control the irrigation flow based on a predetermined command. Keywords : Arduino UNO, irrigation, control system